Odor perception of aromatherapy essential oils with different chemical types: Influence of gender and two cultural characteristics - Chen, Jie; Zhang, Nan; Pei, Shichun; Yao, Lei (Frontiers in Psychology, 2022)
Olfactory perception, and especially affective responses of odors, is highly flexible, but some mechanisms involved in this flexibility remain to be elucidated. This study investigated the odor perceptions of several essential oils used in aromatherapy with emotion regulation functions among college students. The influences of people’s characteristics including gender, hometown region, and fragrance usage habit on odor perception were further discussed. Odor perception of nine essential oils, which can be divided into the ester-alcohol type (e.g., lavender oil) and terpene type (e.g., lemon oil) were evaluated under three odor concentrations. The results indicated that chemical type, but not concentration, significantly influenced the odor perception and there was no interaction between the two factors in this study. The arousal and emotional perception scores of odors with terpene-type oil were significantly higher than odors with ester-alcohol type. In terms of people’s characteristics, participants from the southern Yangtze river gave a higher familiarity rating to almost all of these odors. The habits of fragrance usage also significantly influenced some of the odors' subjective intensity and emotional perception ratings. However, there were no significant gender differences in most of the odor perceptions. In addition, familiarity and pleasantness were positively correlated, and emotional perception and subjective intensity also showed a weak correlation. These results suggested that users’ cultural characteristics could be considered to be important factors that affect the essential oil’s odor perception in aromatherapy.